2020
DOI: 10.1155/2020/3428968
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation Efficiency of Construction Land in China’s Coastal Cities Based on Debt Level

Abstract: Optimising the allocation of population, land, and capital production resources is crucial for promoting an efficient urbanisation and solving the urban land financial problem. This study uses a panel threshold model to identify the response boundary of urban construction land use efficiency to government debt level for 51 postfinancial crisis Chinese coastal cities. The results indicate that the threshold of economic development level and provincial gross domestic product (per capita gross domestic product: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Chen (2017) established a two-sector general equilibrium model to quantify the loss in production efficiency engendered by land misallocation. Some scholars have conducted empirical analyses of China's land market and found that the government's strategic land supply behavior not only causes CLM among sectors and regions but also wastes a large amount of land resources (Du and Peiser, 2014;Wu et al, 2018;Hui Wang et al, 2020). In addition, scholars who discussed related fields, such as capital, labor, and housing market misallocation, could also provide abundant references vis à vis the characteristics of the SMCL (Midrigan and Xu, 2014;Liu and Wong, 2015;Dai and Cheng, 2019;Wu et al, 2020;Shi, 2022).…”
Section: Performances Of the Spatial Misallocation Of Construction Landmentioning
confidence: 99%
“…Chen (2017) established a two-sector general equilibrium model to quantify the loss in production efficiency engendered by land misallocation. Some scholars have conducted empirical analyses of China's land market and found that the government's strategic land supply behavior not only causes CLM among sectors and regions but also wastes a large amount of land resources (Du and Peiser, 2014;Wu et al, 2018;Hui Wang et al, 2020). In addition, scholars who discussed related fields, such as capital, labor, and housing market misallocation, could also provide abundant references vis à vis the characteristics of the SMCL (Midrigan and Xu, 2014;Liu and Wong, 2015;Dai and Cheng, 2019;Wu et al, 2020;Shi, 2022).…”
Section: Performances Of the Spatial Misallocation Of Construction Landmentioning
confidence: 99%
“…Since the reform and opening up, along with the rapid advancement of urbanization and industrialization in China, the amount of urban land has shown a continuous surge. At the same time, the extensive urban land use pattern also leads to a series of problems, such as an unreasonable land structure, disordered land distribution and low land use efficiency [ 2 ]. In the process of rapid urbanization, the excessive consumption of resources and environmental pollution are increasing, and China’s urbanization development is approaching the constraint boundary of resources and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%